2014
DOI: 10.1007/s10792-014-9962-4
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thickness in relation to sex, age, refractive error, and axial length in healthy Turkish subjects

Abstract: The aim of this study was to investigate the association between choroidal thickness (CT) and sex, age, refractive error (RE), and axial length in healthy subjects. This is a study of 154 eyes in 154 healthy subjects. CT measurements were performed by the same experienced technician using a spectral domain optical coherence tomography device. CT was measured perpendicularly from the outer edge of the retinal pigment epithelium to the choroid-sclera boundary at the fovea and at six more points which are located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 29 publications
3
38
1
3
Order By: Relevance
“…Correlation analysis for continuous variables was performed using the Pearson correlation coefficient when indicated. Linear regression analyses were used to compare choroidal thickness among the three groups with adjument for age, gender, and BCVA as these variables have previously been associated with a change in choroidal thickness (19)(20)(21) . Parameters significantly associated with choroidal thickness based on univariate analysis were incorporated into the regression model.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Correlation analysis for continuous variables was performed using the Pearson correlation coefficient when indicated. Linear regression analyses were used to compare choroidal thickness among the three groups with adjument for age, gender, and BCVA as these variables have previously been associated with a change in choroidal thickness (19)(20)(21) . Parameters significantly associated with choroidal thickness based on univariate analysis were incorporated into the regression model.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…1 However, although our understanding of choroidal characteristics has increased substantially in recent years, only a few reports to date have provided values for choroidal thickness in children. [7][8][9] In a recent study, age and axial length (AL) were determined to be negatively correlated with choroidal thickness and volume in adults. 7 Similarly, in a previous study, we also demonstrated a decrease in choroidal thickness with increasing myopia, age, and AL in adults.…”
Section: Introductionmentioning
confidence: 99%
“…7 Similarly, in a previous study, we also demonstrated a decrease in choroidal thickness with increasing myopia, age, and AL in adults. 8 However, although our understanding of choroidal characteristics has increased substantially in recent years, only a few reports to date have provided values for choroidal thickness in children. [9][10][11] Recently, an increase in choroidal thickness with age but an inverse correlation of choroidal thickness with AL was also reported in healthy children aged 3.5-14.9 years.…”
Section: Introductionmentioning
confidence: 99%
“…Turkiye Klinikleri J Ophthalmol 2018;27(1): [39][40][41][42][43][44] daha ince bulunur iken regresyon analizlerinde refraktif kusurun koroid kalınlığı üzerinde büyük etkiye sahip olduğu gösterilmiştir. [37][38][39][40][41] Yapılan ça-lışmalarda, subfoveal koroid kalınlığı/dioptri değişiminin 9,3-13,6 µm olduğu gösterilmiştir.…”
Section: Gereç Ve Yöntemlerunclassified
“…tarafından yapılan çalışmada anlamlı korelasyon izlenmemiştir. 40,43 Çalışmamızda PEX sendromlu bireylerde nazal alanda anlamlı koroidal incelme saptanmış olsa da diğer alanlarda da incelme izlenmiştir. Bu sonuç, PEX sendromunda koroidal dolaşımın materyal birikimi ile etkilendiğini ve koroid kalınlığı-nın azaldığı görüşünü desteklemektedir.…”
Section: Gereç Ve Yöntemlerunclassified